A Giant Retroperitoneal Dedifferentiated Liposarcoma: A Case Report and Comprehensive Review of Multidisciplinary Management - Mohammad Jathy Oktariansyah; Nurudin Syahadat; Fifa Yuniarmi (The International Journal of Medical Science and Health Research, 2025)
Introduction : Retroperitoneal liposarcoma (RLPS) is a rare mesenchymal malignancy characterized by large tumor size at diagnosis and a high propensity for local recurrence. Giant RLPS, particularly the high-grade dedifferentiated subtype, presents formidable diagnostic and therapeutic challenges. Case Illustration : We present the case of a 64-year-old male with a one-year history of progressive abdominal distension. Physical examination revealed a massive, firm abdominal mass. Contrast-enhanced computed tomography (CT) identified a 35 x 25 x 20 cm heterogeneous retroperitoneal mass with both fatty and large non-lipomatous components, consistent with dedifferentiated liposarcoma. The patient underwent an exploratory laparotomy with a successful en bloc compartmental resection, which included the tumor, the right kidney, the right adrenal gland, and a segment of the ascending colon. The resected specimen weighed 10.4 kg. Histopathology confirmed a grade 3 dedifferentiated liposarcoma arising from a well-differentiated liposarcoma, with negative surgical margins (R0). The patient had an uneventful postoperative recovery and is undergoing surveillance. Discussion : This case highlights the central role of radical surgical resection as the only potentially curative modality for primary RLPS. The discussion provides a comprehensive review of the diagnostic utility of cross-sectional imaging, the principles of compartmental surgery to achieve negative margins, and the current, evolving landscape of adjuvant therapies. We critically analyze the results of the landmark EORTC-STRASS trial, which failed to show an overall benefit for preoperative radiotherapy but suggested a potential benefit in the liposarcoma subgroup, creating an ongoing clinical controversy. The limited role of systemic therapy outside of the advanced or metastatic setting is also reviewed. Conclusion : The management of giant RLPS is complex and necessitates a multidisciplinary approach at a specialized sarcoma center. Complete surgical resection remains the cornerstone of treatment, while the role of neoadjuvant therapies continues to be refined through histology-specific clinical trials.